Pengelolaan sempadan danau di kawasan pertanian: ulasan bandingan Polandia, Tiongkok dan Indonesia - Permatasari, Prita Ayu; Koestoer, Raldi Hendro Toro Seputro (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2022)
High anthropogenic activities have an impact on land use change that threatens lake ecosystems in various parts of the world. The socio-economic condition of the local community is one of the main factors affecting land use on the lakeshores. Government policies related to lake protection are important in the lake ecosystems management, especially land use in the lakeshore zones. This paper aimed to investigate lake management in agricultural areas in various countries such as Poland, China, and Indonesia. By conducting this comparison, management of the lake ecosystems including the land use of the surrounding area have been discovered. Through case study analysis and policy analysis issued by the central government, the positive and negative effects of each policy related to lake management could be obtained. The results showed that in several European countries, the trend of lakes utilization for tourism areas is increasing. China, a country with rapid economic growth, has begun to restore agricultural land into wetlands and lake ecosystem. Meanwhile, the high demand for food in Indonesia causes agricultural areas in the lakeshore zones difficult to convert.